Reliability, sensitivity, and minimal detectable change of a new specific climbing test for assessing asymmetry in reach technique - Cular, D.; Dhahbi, W.; Kolak, I.; Iacono, A. D.; Bešlija, T.; Laffaye, G.; Padulo, J. (The Journal of Strength and Conditioning Research, 2021)
The aims of this study were to establish intertrial and intersession reliability, sensitivity, and minimal detectable change of a new climbing test specifically for assessing asymmetry in reach technique (TEST). Twenty-four young climbers (16 males and 8 females) participated in this study. The protocol consisted of performing, in counterbalanced random order, 3 tests; TEST, maximum handgrip force, and squat on the bench, in 2 sessions (with 3 trials for each session). TEST performance was expressed as: TEST performance for left hand (TESTL), TEST performance for right hand (TESTR), and absolute symmetry index (ASI). For intertrial and intersession reliability assessment, TESTL and TESTR showed excellent reliability (intraclass correlation coefficients ranged: 0.96-1.00; SEM% ranged: 0.07-1.23; and coefficient of variation—CV%: 1.28-2.53). In addition, SEMs were smaller than the smallest worthwhile change (SWC) values (SWC% = 1.07 and 0.99 for TESTL and TESTR, respectively), and the minimal detectable change (MDC95) for both sides was small (<4.36 cm). An exception was ASI, which showed low absolute reliability and marginal sensitivity (SEM% = 15.13 > SWC% = 8.40 and CV% = 41.98). Pairwise test comparisons revealed no difference between sides. Considering the high reliability and the satisfactory sensitivity, TEST can be used to define individual asymmetry in the performance of the reach technique to the left or the right body side in climbers. However, interpreting data using the ASI index requires caution because it had poor absolute reliability and marginal sensitivity.